PENGEMBANGAN DESA WISATA AGROEDUWISATA DI DESA PETIYENTUNGGAL: PENGEMBANGAN DESA WISATA AGROEDUWISATA DI DESA PETIYENTUNGGAL - Moh. Hudi; Muhammad Nilson Ikmaludin; Diva Vania Gatot (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
The Agro-edutourism-based tourism village is the first in Petiyentunggal Village and Gresik Regency. This Agroedutourism Tourism Village was initiated by the Village Head and POKDARWIS which is under the auspices of BUMDES Petiyentunggal Village. The concept created provides an attractive bargaining power, as the name suggests, namely (1) agro has fruit and flower tourism, (2) edu has education on sowing or breeding, grafting and transplanting, and (3) tourism has swimming pools, mini animal gardens, and homestays.